New version of fermi-walker derivatives according to the type-2 bishop frame with energy - Körpınar, Talat; Özdemir, Hatice; Körpınar, Zeliha (EDITURA BIBLIOTHECA-BIBLIOTHECA PUBL HOUSE, 2021)
In this paper, we obtain the Fermi-Walker derivatives of xi(1), xi(2), B magnetic curves according to the type-2 Bishop frame in the space. Moreover, we obtain the energy of the Fermi-Walker derivative of magnetic curves according to the type-2 Bishop frame in space. Finally, we have energy relations of some vector fields associated with type-2 Bishop frame in the space.
Keywords: magnetic curve; Lorentz force; type-2 Bishop frame; Fermi-Walker derivative; energy